Temporal Variability of Equatorial Ionization Anomaly Crest Locations Extracted From Global Ionospheric Maps - Corina Dunn; Xing Meng; Olga P. Verkhoglyadova (Space Weather)
Abstract The Equatorial Ionization Anomaly (EIA) crest location is known to vary over a variety of temporal scales. For the first time we perform a statistical survey of the temporal variation of the EIA crest location viewed globally and spanning 20 years. We extract the crest location for double‐peaked EIAs from a data set of total electron content intensifications identified on global ionospheric maps from 2003 to 2022. We show that the dominant temporal variations of the crest latitude are annual and semi‐diurnal for the northern crest, and annual and diurnal for the southern crest. For the annual variation, we find that both crests move poleward in local summer and equatorward in local winter, which is more pronounced for the southern crest than the northern crest, and more pronounced at solar minimum than solar maximum. For the diurnal and semi‐diurnal variations in universal time, both crests dip southward around 15UT and the northern crest additionally dips southward around 2.5UT. We consider apparent universal time dependence to be a proxy for the longitudinal distribution of the crest geomagnetic latitude, which exhibits the known wave‐number‐four longitudinal structure of EIA crests. In local time, the EIA crests form earlier than 10LT and move poleward to their maximum distance at 14LT, and remain at constant latitude until 18LT. Solar cycle modulation on the diurnal/semi‐diurnal variations and the local time evolution of the crest latitude is minimal.